The Effect of Endosulfan Pesticide in Some Biochemical Parameters of white Mice - Abd-Alkazem, Diyana M.; Rabee, Adel M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The present study aimed to examine the effect of endosulfan insecticide on some molecular and biochemical parameters in white mice. Thirty mice were separated randomly into three groups for treatment with endosulfan. One group (G1) served as the control, while the other two groups received intraperitoneal injections of endosulfan G2 (3 mg/kg) and G3 (17 mg/kg) twice a week for 21 and 45 days, respectively. A biochemical study by measuring liver function parameters, including (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)) and kidney function parameters, including (Blood Urea and Creatinine) and malondialdehyde (MDA), catalase activity (CAT). This study also tested DNA damage by comet assay (normal%, low%, medium%, high%). The results of renal function parameters (Blood Urea and Creatinine) were significantly increased in all treated groups after 21 and 45 days exposed to endosulfan compared with control groups. The highest value of blood urea recorded was (49.33 ±0.88 mg/dl) at 17 mg/kg for 45 days compared with the control group, and the highest value of Creatinine recorded was (1.81 ±0.13 mg/dl) at 17 mg/kg for 45 days compared with the control group. Liver function parameters (ALT and AST) significantly increased in all treated groups compared with control groups. The results of MDA, CAT enzyme, were significantly increased in all treated groups after 21 and 45 days compared with control groups. The highest value of MDA recorded was (3.93 ±0.07 μM) at 17 mg/kg for 45 days compared with the control group. Tail DNA (%) showed a significant increase at high concentrations, and the results showed a considerable increase in the severe damage of DNA in the treated group 17 mgb.wt. (25.00 ±1.00)% for 45 days, compared with the control group (3.00 ±1.00) %.